Výsledky implantace trifokální torické čočky u pacientů s kataraktou - Brožková, M; Filipec, M; Filipová, L; Holubová, A; Hlinomazová, Z (Ceska a slovenska oftalmologie, 2016)
AIM: The aim of our study was to evaluate the outcome of cataract surgeries with implantation of intraocular trifocal toric lens, and to study the accuracy of astigmatism correction, lens rotational stability, and safety of the procedures. PATIENTS AND METHODS: Our study comprised 22 eyes of 16 patients who underwent unilateral or bilateral implantation of AT LISA tri toric 939MP, or its implantation in combination with AT LISA tri 839MP. Mean patient age was 58 ± 11 years (39 to 75 years). Mean follow-up was 5 months. Evaluated parameters were preoperative and postoperative decimal corrected (CDVA) and uncorrected (UDVA) distance visual acuity. Uncorrected near (UNVA) and intermediate (UIVA) visual acuity was obtained with Jaeger optotypes. Furthermore, we studied manifest refraction, amount of corneal astigmatism, implanted lens position, and potential complications. Using two types of questionnaires we surveyed patients on their subjective satisfaction with vision. RESULTS: Spherical equivalent changed from preoperative -1.32 ± 4.05 D (-9.25 to 4.00 D) to postoperative -0.23 ± 0.21 D (-0.75 to 0.00 D). Preoperative corneal astigmatism was -1.97 ± 0.76 D (-4.02 to -1.01 D), manifest astigmatism was -1.70 ± 1.26 D. After the surgery, manifest astigmatism significantly improved to -0.34 ± 0.37 D (p<0.001). Mean monocular UDVA increased from 0.26 ± 0.18 (0.05 to 0.60) to postoperative 0.88 ± 0.13 (0.60 to 1.00) (p<0.001). CDVA also improved significantly, from 0.57 ± 0.24 to a final value of 1.02 ± 0.07 (p<0.001). Mean postoperative monocular UNVA was Jaeger 1-2, UIVA corresponded to Jaeger 3-4.No serious complications were recorded. Based on the outcome of questionnaires, all patients are satisfied with their vision and they are independent of spectacles. CONCLUSION: In the present study we have obtained very good functional outcomes of vision at far, near and intermediate in cataract patients after trifocal AT LISA tri toric lens implantation. Also, total astigmatism in studied eyes was substantially reduced. The treatment led to a high subjective satisfaction of patients and to their independence of spectacles. KEY WORDS: trifocal toric intraocular lens, cataract, astigmatism, refractive outcomes, patient subjective satisfaction.
Keywords: výsledek terapie; spokojenost pacientů; Male; zraková ostrost; Prosthesis Design; implantace nitrooční čočky; protézy - design; Lenses, Intraocular; Cataract; následné studie; Pseudophakia; pseudofakie; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; Patient Satisfaction; průzkumy a dotazníky; Visual Acuity; Follow-Up Studies; Treatment Outcome; katarakta; nitrooční čočky; lidé; ženské pohlaví; Lens Implantation, Intraocular; Humans; refrakce oka; Phacoemulsification; Female; fakoemulzifikace; Refraction, Ocular; Surveys and Questionnaires; lidé středního věku; Middle Aged; prospektivní studie